MANAJEMEN EKSTRAKURIKULER PRAMUKA - Dewi Ariani Dewi Ariani (Manajer Pendididikan, 2015)
The objective of this research was to compare the differences and similarities the management of scout extracurricular activities between public Junior High School Number 1 andNumber 4 in Bengkulu City. The subjects of this study were the teachers, principals and students. The technique of collecting data were interview, observation and documentation. The results of research show that the scout management at both school has the differences and similarities in the planning,organizational structure, implementation, monitoring and evaluation. The differences in include details of the work program, scouts membership, exercise time, system monitoring and evaluation and barriers that faced. The similarities is the purpose of the organization that wants to from students ofcharacter have independence, brave, discipline and responsible.Keyword: management, scout extracurricular activities